ACE inhibitor angioedema: characterization and treatment versus non-ACE angioedema in acute hospitalized patients. Issue 1 (2nd January 2020) - Weisman, David S.; Arnouk, Nelly; Asghar, M. Bilal; Qureshi, M. Raheel; Kumar, Anagha; Desale, Sameer; Camire, Lyn; Pineda, Stephen
ABSTRACT: Background: ACE angioedema has not been characterized in comparison with angioedema from other causes in acute hospitalized patients. Methods: We retrospectively compared ACE-angioedema and non-ACE angioedema patients from January 2013 to May 2017. Results: Of 855 cases screened, 575 met the inclusion criteria of angioedema diagnosis and an electronic medical record. Of these, 297 (51.7%) had ACE angioedema and 278 had angioedema from other causes, of these 31 who were taking an ACE inhibitor that was not considered to be the cause of angioedema (ACE other cause). At least 80% of cases in all groups were African American. Epinephrine was prescribed in 21% of ACE angioedema cases. One-third of patients in all groups were admitted to the ICU, and about 25% required intubation. Previous history of ACE inhibitor-induced angioedema was found in 63 of 278 non-ACE cause angioedema patients (23%) and in 23 (8%) in the ACE cause group. Conclusion: ACE angioedema was the cause of half of angioedema admissions over a 4.5-year period. Mortality, morbidity, and treatment did not differ between the groups. Patients on ACE inhibitors were often treated with medications known not to be effective for ACE angioedema. Over one-fourth of patients not taking an ACE inhibitor had a previous history of ACE angioedema, and 31 patients taking ACE inhibitors were diagnosed with non-ACE angioedema. Regardless of the etiology of angioedema, 25% of patients required airway protection in the form of intubation.